2019
DOI: 10.1108/ijopm-02-2018-0057
|View full text |Cite
|
Sign up to set email alerts
|

Digital health technology enhances resilient behaviour: evidence from the ward

Abstract: Purpose In the healthcare management domain, there is a lack of knowledge concerning the role of resilience practices in improving patient safety. The purpose of this paper is to understand the capabilities that enable healthcare resilience and how digital technologies can support these capabilities. Design/methodology/approach Within- and cross-case research methodology was used to study resilience mechanisms and capabilities in healthcare and to understand how digital health technologies impact healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 80 publications
2
76
0
Order By: Relevance
“…Wang et al [55] confirmed the impact of IT support in enhancing educators' resilience to keep working even during the pandemic. Another study on healthcare practitioners affirmed the significance of accessible IT infrastructure and services in building healthcare workers' resilience, which, in turn, guarantees patient safety [56]. Hence, we posit that the provision of facilitating conditions, such as the availability of relevant IT infrastructure and services, could enhance employees' resilience.…”
Section: Effect Of Facilitating Conditions On Resiliencementioning
confidence: 78%
“…Wang et al [55] confirmed the impact of IT support in enhancing educators' resilience to keep working even during the pandemic. Another study on healthcare practitioners affirmed the significance of accessible IT infrastructure and services in building healthcare workers' resilience, which, in turn, guarantees patient safety [56]. Hence, we posit that the provision of facilitating conditions, such as the availability of relevant IT infrastructure and services, could enhance employees' resilience.…”
Section: Effect Of Facilitating Conditions On Resiliencementioning
confidence: 78%
“…Moving from the individual to a team-based perspective, the paper by Rubbio et al (2020) in this special issue draws on dynamic capabilities theory to explore how surgery wards in two Italian hospitals employ resilient behaviour to solve operational failures and improve patient safety. As such, it studies the effect of team decisionsa ward's nurses and physicianswithin a larger organisation.…”
Section: Four Levels Of Scres and The Contributions Of The Special Ismentioning
confidence: 99%
“…Indeed, building SCRes can require organisations and supply chains to contribute to resilience at an industry, national or supranational level. The paper by Rubbio et al (2020) contained in this special issue is a starting point for such research. To the best of our knowledge, it is the first to extend SCRes to the healthcare sector.…”
Section: Scres Level 4: Sectors National and Supranationalmentioning
confidence: 99%
“…Further in-depth analysis on enhancing the resilience of FSCs in food industries is essential to address the complex risks. Moreover, few studies have explored sector-level resilience, which requires the FSC to contribute to resilience at the industrial, national, or supranational level [28]. This study covers a huge gap in the literature of the FSCs problem at hand through reviewing and analyzing the up-to-dated studies to assess the disruptions and build a resilient FSC to achieve food security at the sector level.…”
Section: Research Gapsmentioning
confidence: 99%